The associations of working hour characteristics with short sickness absence among part- and full-time retail workers - Rahman Shiri; Tarja Hakola; Mikko Härmä; Annina Ropponen (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVE: This study aimed to determine the associations of working hour characteristics with short (1-3 days) sickness absence (SA) among retail workers. METHODS: As part of "RetailHours-project", 4046 employees of 338 Finnish retail stores were included. Registry-based data on working hour characteristics and short SA were utilized. A case-crossover design was used and the odds ratios (OR) were controlled for the clustering effect and working hour characteristics. RESULTS: There were strong dose-response relationships between percent of short (<11 hours) shift intervals and short SA among part- and full-time workers, men and women, and younger and older workers. Compared to workers without short shift intervals, the risk of SA was 1.47 times [95% confidence interval (CI) 1.29-1.68] higher among workers who had short shift intervals <10% of work times, 2.39 times (95% CI 2.03-2.82) higher among workers who had 10-25% of work times, and 4.03 times (CI 2.34-6.93) higher among workers who had short shift intervals >25% of work times. Weekly working hours >40 hours were associated with SA among part-time workers [odds ratio (OR) 2.22, CI 1.65-2.98], women (OR 1.62, CI 1.27-2.07) and among workers <30 years of age (OR 1.68, CI 1.20-2.35) as well as among workers aged ≥30 years (OR 1.43, CI 1.07-1.92). Furthermore, working mainly night shifts was associated with SA among full-time workers (OR 2.41, 95% CI 0.99-5.86) and women (OR 1.72, CI 1.02-2.89). CONCLUSIONS: A short shift interval is an important risk factor for short SA. Improving intervals between shifts and shortening long weekly working hours could reduce the risk of short SA among retail workers.